Implikasi Kebijakan Pendidikan dalam Mengurangi Kemiskinan dan Ketimpangan - Sarjito, Aris (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2024)
This research aims to explore the relationship between education, poverty reduction, and income inequality. It investigates the pathways through which education can promote social mobility and reduce income inequality, as well as the extent to which education mediates the relationship between poverty and inequality. A qualitative research method using secondary data analysis is employed. Various sources, including academic articles, reports, and surveys, were reviewed to extract relevant information regarding education, poverty, and inequality. Data were analyzed thematically to identify patterns, trends, and correlations. The research findings highlight that education plays a crucial role in reducing poverty and income inequality. It serves as a vehicle for social mobility by providing individuals with skills, knowledge, and opportunities for upward economic mobility. Education is found to mediate the relationship between poverty and inequality by equipping individuals with the necessary tools to escape the poverty trap and access better job prospects and income levels. Socioeconomic factors significantly influence the impact of education on poverty and inequality. Disparities based on gender, ethnicity, and geographical location are reported, indicating the need for targeted interventions to ensure equal access to quality education.